IMPROVING STUDENTS’ READING COMPREHENSION USING SUGGESTOPEDIA IN TEACHING NARRATIVE TEXT - Anjellia Harimu; Nihta Liando; Paula Rombepajung (Program Studi Pendidikan Bahasa Inggris, 2022)
Reading comprehension is the ability to process text, understand the meaning of the text and not what the reader knows. The ability of individuals to understand texts is influenced by their skills and their ability to process information. Seeing the importance of reading comprehension in the process of learning English from students, the researcher wanted to see how to use suggestopedia to improve students' reading comprehension. As is well known, suggestopedia is a learning method that aims to make students feel relaxed and relieve tension in learning. In this study, the researcher used a quantitative method by applying a one group pre-test and post-test design. The subjects in this study were students from Berea Tondano Junior High School in class VIII with a total of 20 students as a sample. In measuring the extent to which suggestopedia affects students' reading comprehension, the researcher uses a test that is given at the beginning and at the end of the treatment. As a finding, suggestopedia has a very positive effect on students' reading comprehension, which can be seen from the increase in students' scores from pre-test to post-test. In addition, suggestopedia has the following effects: (1) gives peace and relaxation; (2) pleasant or exhilarating; (3) accelerate the learning process; (4) emphasizes the development of language skills.